Relative ranking of ornamental flower plants to foraging honey bees (with notes on favorability to bumble bees) - Cranshaw, Whitney, author; Colorado State University, Department of Bioagricultural Sciences and Pest Management, publisher (Colorado State University. Libraries, 2010)
Observations were made during the 2007-2009 growing seasons on the relative attractiveness of various flowering ornamental plants to honey bees (Apis mellifera). This information was collected so that honey bee favorability - or lack of favorability - may be considered in plant selection.
Date inferred from file name.
Keywords: Insect populations -- Colorado; Bees -- Habitat -- Colorado